EFFECT OF IONIC STRENGTH ON ION EQUILIBRIUM IN SMUF - Faridah, Faridah; Ridwan, Ridwan (Jurnal Sains dan Teknologi Reaksi, 2009)
The influence of monovalent cations on ion equilibria in SMUF such as NaCl and KCl. The free Ca2+ and Mg2+ ion activity and concentration and phosphate concentration in SMUF were determined at different concentrations of NaCl and KCl. Free Ca2+ and Mg2+ concentration increased with added NaCl and KCl, while pH decreased. It was found that adding NaCl lead to higher Ca2+ and Mg2+ concentration than adding KCl. The difference between Na and K in free Ca2+ and Mg2+ concentration can be well explained by the charge density theory by Collins. An ion speciation model was used to calculate ion speciation in SMUF and model prediction was in general agreement with Ca-ISE and DMT results in the case of adding NaCl and KCl. Moreover, pH decreased by time, indicating kinetics involved in calcium phosphate precipitates.Key words: Calcium, Magnesium, pH, KCl, NaCl, SMUF, Ca-ISE, DMT, ion speciation model